Determination of Breast Self-Examination Behaviors and Beliefs in Nursing Students During the Pandemic Process - Yüksekol, Özlem Doğan; Nazik, Feyza; Yılmaz, Ayşe Nur; Erbek, Özkan; Tanrıkulu, Şerna (Ondokuz Mayıs University, 2022)
Aim:This research was carried out to determine nursing students' self-breast examination (BSE) behaviors, health beliefs and factors that may affect them during the pandemic process. Method:The sample of this cross-sectional and descriptive study consisted of 168 students studying in the nursing department of a public university in Eastern Turkey. The data were collected online with the "Personal Information Form" and the "Health Belief Model Scale in Breast Cancer Screening". The scale has six sub-dimensions: sensitivity, caring-seriousness, health motivation, BSE benefits, BSE barriers, and self-efficacy. Descriptive statistics, independent samples t test, one-way anova, mann-whitney U test, kruskall-wallis test and mc nemar test were used in the analysis of the data. Results:The average age of the students is 20.8±1.3. 34% of students are in the second year. The incidence of breast cancer in the family of students is 6%. 75% of the students stated that they heard BSE. The rate of students getting information about BSE is 70.2%. BSE application status was 37.5% before the pandemic and 14.9% after the pandemic(p

Amaç:Bu araştırma, pandemi sürecinde hemşirelik öğrencilerinin kendi kendine meme muayenesi (KKMM) davranışlarını, sağlık inançlarını ve etkileyebilecek faktörleribelirlemek amacıyla yapıldı. Yöntem:Kesitsel ve tanımlayıcı türde olan bu araştırmanın örneklemini, Türkiye’nin doğusunda bulunan bir kamu üniversitesinin hemşirelik bölümünde öğrenim gören 168 öğrenci oluşturdu. Veriler, “Kişisel Bilgi Formu”ile “Meme Kanseri Taramalarında Sağlık İnanç Modeli Ölçeği” ile online olarak toplandı.Ölçeğin duyarlılık, önemseme-ciddiyet, sağlık motivasyonu, kendi kendine meme muayenesi (KKMM) yararları, kendi kendine meme muayenesi engelleri ve öz-etkililik olmak üzere altı alt boyutu bulunmaktadır. Verilerin analizinde tanımlayıcı istatistikler, independent samples t testi ve one-way anova, mann-whitney U testi, kruskall-wallis testleri ve mc nemar testi kullanıldı. Bulgular: Öğrencilerin yaş ortalaması 20.8±1.3’tür. Öğrencilerin %34’ü ikinci sınıftadır. Öğrencilerin ailesinde meme kanseri görülme oranı %6’dır. Öğrencilerin %75’i KKMM’yi duyduklarını belirtmişlerdir. Öğrencilerin KKMM hakkında bilgi alma oranı %70.2’dir. Pandemi öncesi KKMM uygulama durumu %37.5, pandemi sonrası %14.9’dur (p
PANDEMİ SÜRECİNDE HEMŞİRELİK ÖĞRENCİLERİNDE KENDİ KENDİNE MEME MUAYENESİ DAVRANIŞ VE İNANÇLARININ BELİRLENMESİ
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi